Circular Economy In Mataram City Waste Management: Opportunities, Challenges, And Implementation Strategies - An Nisa Rauhul Fauziah; Moh. Huzaini; M. Firmansyah M. Firmansyah (JURNAL ECONOMINA, 2026)
This study aims to analyze the condition of waste management, identify opportunities and challenges in implementing a circular economy, and formulate a strategy for implementing a circular economy in waste management in Mataram City. This study uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation involving the government, business actors, communities, waste bank managers, and the public. Data analysis is carried out through data reduction, data presentation, drawing conclusions, and SWOT analysis. The results show that waste management in Mataram City is still in the transition stage towards a circular economy and is dominated by a linear pattern (collect-transport-dispose). The implementation of a circular economy has opportunities through the availability of waste as raw material, waste processing innovation, policy support, and increased community participation. However, its implementation still faces challenges such as low waste sorting at source, limited facilities and infrastructure, and an unintegrated waste management system. Based on the SWOT analysis, the recommended priority strategy is the Weakness-Opportunities (WO) strategy through increasing education and community participation, strengthening collaboration between actors, and developing facilities and infrastructure for circular economy- based waste management. This study found that the implementation of the circular economy in Mataram City is still in a partial transition state, namely when various elements of the circular economy have developed, but have not yet formed a complete and sustainable waste management system.